Ethnic groups in conflict - Horowitz, Donald L. ([S.l.] : University of California Press, 1987)
Drawing material from dozens of divided societies, Donald L. Horowitz constructs his theory of ethnic conflict, relating ethnic affiliations to kinship and intergroup relations to the fear of domination. A groundbreaking work when it was published in 1985, the book remains an original and powerfully argued comparative analysis of one of the most important forces in the contemporary world.
Keywords: Developing countries; Ethnic conflict; Ethnic groups--Political activity; Ethnic relations; Social conflict